Cerebral Amyloid Angiopathy: An Undeniable Small Vessel Disease - Litao Wang; Qiong Liu; Dongqi Yue; Jun Liu; Yi Fu (Journal of Stroke, 2024)
Cerebral amyloid angiopathy (CAA) has been proven to be the most common pathological change in cerebral small vessel disease except arteriosclerosis. In recent years, with the discovery of imaging technology and new imaging markers, the diagnostic rate of CAA has greatly improved. CAA plays an important role in non-hypertensive cerebral hemorrhage and cognitive decline. This review comprehensively describes the etiology, epidemiology, pathophysiological mechanisms, clinical features, imaging manifestations, imaging markers, diagnostic criteria, and treatment of CAA to facilitate its diagnosis and treatment and reduce mortality.